Adsorption of NH3 with Different Coverages on Single-Walled ZnO Nanotube: DFT and QTAIM Study - Marana, Naiara L. [UNESP]; Casassa, Silvia M.; Sambrano, Julio R. [UNESP] (American Chemical Society (ACS), 2017)
NH3 adsorption with different coverages on single-walled armchair and zigzag ZnO nanotubes (ZnONT) has been studied via periodic computational simulations at the all-electron B3LYP level. In order to fully characterize the molecules-surface interaction, infrared (IR) spectra were calculated for the first time. A rigorous analysis of the electron density in the bonding region, according to the quantum theory of atoms in molecules, was performed. NH3 molecules physisorb without dissociation via a self-catalyzed process. Although the nanotubes undergo sensitive lattice deformations with low coverages, its fundamental electronic properties were not modified. Owing to these analyses, the ZnONTs can be applicable as NH3 gas sensor. (Chemical Equation Presented).